(untitled) (Modern education and development, 2024)
Uterine prolapse is a variant of pelvic floor dysfunction. Every third patient experiences this condition, which in half of the cases is accompanied by urinary incontinence. Recently, there has been a “rejuvenation” of the disease. Not only women who have given birth can experience uterine prolapse, but also young girls, since the cause of the development of this condition may be the characteristics of the connective tissue.